The Effect of DER And PBV on Stock Price in Companies Listed of The Consumer Cyclicals Sector - Roviska, Nashwa Wanda; Meirisa, Faradila (Jurnal Multidisiplin Sahombu, 2025)
This study analyzes the effect of Debt to Equity Ratio (DER), and Price to Book Value (PBV) on Stock Price in Companies Listed of the consumer cyclicals sector period on 2021-2023. By using hypothesis testing, the research sample consisted of 126 companies. The results showed that DER does not have a significant influence on the stock prices of companies in the Consumer Cyclicals sector and PBV had an effect on Stock Price. Simultaneously, these two variables have a significant influence with an Adjusted R² of 9%, indicating that other factors also affect Stock Price.